2023
DOI: 10.3389/fsurg.2022.1049933
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms to predict atypical metastasis of colorectal cancer patients after surgical resection

Abstract: BackgroundThe prognosis of colorectal cancer with atypical metastasis is poor. However, atypical metastasis was less common and under-appreciated.MethodsIn this study we attempted to present the first machine learning models to predict the risk of atypical metastasis in colorectal cancer patients. We evaluated the differences between metastasis and non-metastasis groups, assessed factors associated with atypical metastasis using univariate and multivariate logistic regression analyses, and preliminarily develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The predictive performance of the LR remained outstanding, with an AUC of 0.96 (95% CI: 0.75-0.97) for DFS and 0.92 (95% CI: 0.66-0.92) for OS. Given these compelling results, we concluded that single clinicopathological classifiers exhibit robust efficacy (38,39). To further validate our predictive model, we applied it to an external validation cohort.…”
Section: /42mentioning
confidence: 97%
“…The predictive performance of the LR remained outstanding, with an AUC of 0.96 (95% CI: 0.75-0.97) for DFS and 0.92 (95% CI: 0.66-0.92) for OS. Given these compelling results, we concluded that single clinicopathological classifiers exhibit robust efficacy (38,39). To further validate our predictive model, we applied it to an external validation cohort.…”
Section: /42mentioning
confidence: 97%